Neutral Stochastic Impulsive Integro-Differential Equations Driven by Fractional Brownian Motion and Brownian Motion with Nonlocal Condition - Abinaya, S.; Jose, Sayooj Aby; Sudsutad, Weerawat (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we present the existence, uniqueness and asymptotic behaviour of mild solution for neutral stochastic impulsive integro-differential equations driven by fractional Brownian motion and Brownian motion with the Hurst index $H>\frac{1}{2}$ with nonlocal condition. The results are obtained by using Banach fixed point principle in a Hilbert space and the theory of resolvent operator.